Evaluation of parabolic shaped solar dryer (PSSD) for drying of tomatoes under semi-arid climate zone - Jude Joel; Abba Kaka Alkali; Bala Ibrahim; Abubakar Ahmad Adamu; Fatima Jamu Babba; Oshadumo Dayo (Discover Food)
Abstract This study aimed to evaluate the performance of a Parabolic Shaped Solar Dryer (PSSD) developed at Nigerian Stored Products Research Institute (NSPRI) Kano for drying Tomatoes compared to traditional Open Sun Drying methods. During the experiment, 139.3 kg of Tomato slices of Eka variety with 5 mm thickness were dried in the Parabolic Shaped Solar Dryer. The drying rate, physiochemical properties, functional properties, and bacteria count were determined. The result showed that Parabolic Shaped Solar Dryer recorded a maximum temperature of 68.2 °C, and a drying rate of 5.2 kg/day leading to a moisture content of 14.5% within the 6 days drying period. In contrast, Open Sun Drying resulted in a slightly higher moisture content of 17.8%, a lower drying rate of 1.3 kg/day, and a maximum temperature of 47.5 °C. The result also indicates an increase in Titratable acidity while Vitamin C retention significantly declines in both drying systems. A decrease in pH and Total Soluble solids was also observed. Oil Absorption capacity was observed to be 10% higher in a Parabolic Shaped Solar Dryer than in Open Sun Drying while Water Absorption capacity was also highest in samples dried in Parabolic Shaped Solar Dryer. Compared to Open Sun drying; Parabolic Shaped Solar dried tomatoes showed a much better nutrient retention for all quality parameters.